Analysis and Modelling of Matrix Converter as a Frequency Changer - Pandit Sidharth (My University, 2017)
From the last few years, there is a continuous increase in the use of electronics converters like AC to AC converters AC to DC or DC to AC converters. So, there is a requirement of devices with generates fewer harmonics, minimum switching losses and generate the high quality desired waveforms in input and output. It stimulates the researchers to innovate new ideas to minimize these effects. In this thesis, the main focus is to design and Implementation of Matrix Converter (MC) for frequency changing applications. In this thesis, space vector based PWM mechanism is used to design a mathematical model of single phase and three phase Matrix Converter. There is no DC link between rectifier and inverter stage which add up some efficient properties like compact design, bi-directional current flow capabilities. Along with that it has demerits like maximum output input voltage ratio is low and these systems are not commercially available and require more research on this converter to make it available commercially. This thesis work analyses some novel achievements reported in recent literature. For the supply application of the MC, a comparative analysis has been done and implemented on different MC models. MC control strategies have been implemented for SPMC and TPMC. Simulation work is done in MATLAB Simulink environment and comparison with mathematical results is presented.
Master of Engineering -Power Electronics & Drives
Keywords: Matrix Converter; SPMC- Single Phase Matrix Converter; TPMC Three Phase Matrix Converter; SVPWM; Rectifier; Inverter.